AKIBAT HUKUM TERHADAP AKTA NOTARIS YANG MELANGGAR KETENTUAN PASAL 41 UUJN - Rusida, Enti (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2024)
Article 41 UUJN explains that violations of the provisions as intended in Articles 38 to Article 40 result in the deed only having the power of proof as a private deed. That the articles confirmed in Article 41 are regarding the conditions for the validity of an agreement as confirmed in Article 1320 which should result in the deed being canceled or null and void by law. Based on this problem, the first formulation of the problem is what the legal consequences should be for a notary's deed which violates the provisions of Article 41 UUJN and secondly what is the difference between a deed being relegated to a private deed and a deed that can be canceled or null and void by law. This research method is normative or doctrinal, the object of which is statutory regulations with a case and doctrinal approach, then the primary legal material is statutory regulations and the secondary legal material is books. The results of this research are that firstly, if a notarial deed violates the provisions of Article 41 UUJN, it should not result in the deed only having the power of proof as a private deed or degraded to an underhand deed, but it should be null and void, secondly, the difference between a deed that is degraded becomes a private deed. with nullity by law is based on the strength of the evidence and that if the deed becomes a private deed, it means that the deed has fulfilled the elements of Article 1320 or the conditions for the validity of an agreement, while null and void is a deed that violates or does not fulfill the elements of Article 1320. The suggestion is that Article 41 UUJN should be revised or changed so that it is in line with applicable law, namely that the legal consequence should be that it is null and void and not a private deed.